Effects of Self-Weighing During Weight Loss Treatment: A 6-Month Randomized Controlled Trial - Hernández-Reyes, Alberto; Cámara-Martos, Fernando; Vidal, Ángela; Molina-Luque, Rafael; Moreno-Rojas, Rafael (Frontiers in Psychology, 2020)
Objective To examine the effectiveness of self-weighing for weight loss in men for 6 months. Methods In the present study, 54 men, mean age of 40.1 ± 11.1 years, with overweight or obesity, were recruited and randomly assigned into two groups: control group (CG), without weight self-monitoring and intervention group (IG), with weight self-monitoring. Both groups received the same nutritional and educational advice and the establishment of a weight target to reach in the weight loss program. Subjects of IG also had individualized motivating content to improve self-management for 24 weeks. Anthropometric indices were measured at baseline and weekly for 24 weeks. Results When the group assigned after randomization was introduced in the analysis, its influence was significant in weight loss (F1.52 = 19.465, ± 2 = 0.272, p < 0.001) and in the decrease in body fat percentage (F1.52 = 8,306, ± 2 = 0.132, p < 0.01). Conclusion Study results indicate that self-weighing can help patients to lose additional weight. Our findings have implications in the emerging area of the behavioral approach of patients undergoing weight-loss treatment, as well as clinical care processes. Clinical Trial Registration www.ClinicalTrials.gov, identifier NCT04032249.